Chemical Ecology and Volatile Terpenes Biosynthesis of Arnicas-da-Serra from Brazil - Pavarini, Daniel P. [UNESP]; Lopes, Norberto P. (Brazilian Chemical Soc, 2016)
Lychnophora (Vernonieae: Asteraceae) is a genus endemic to campos rupestres, which are fragile Habitats from Brazilian Savanas, the Cerrado. Leaves extracts of Lychnophora ericoides (Arnica-da-serra) are commonly used as folk medicine and mainly as wound healer when in Hydro-alcoholic handcrafted medicines. The essential oils from its leaves were chemically profiled as rich in sesquiterpenes. Such sesquiterpenes would always be related to three possible carbon skeletons: bisabolene-like, cadinene-like, and caryophilllene-like carbon skeletons. L. ericoides leaves essential oils are bioactive against invertebrate Acari. An anti-hypernociceptive ability of its component orto-acetoxy bisabolol was also displayed by in vitro assays using Ratus malus macrophages. Terpenes compounds are valuable in fine chemistry industry, e.g. Taxol (R) and Acheflan (R). Furthermore, terpene synthases (TerpS) behind their biosynthesis are target of researches in plant sciences and biochemistry. Identification of TerpS often led to conclusions with diverse impacts. Fundamental concepts on time-dependent shifts of terpene productions in wild type species as well as the advances towards plant metabolites bioengineering are examples of such impacts. Our brief review tends to provide the reader an overview of phytochemical relevance of Lychnophora spp., regard both ecological and pharmaceutical traits. Furthermore, an introduction to dynamics aspect of terpene biosynthesis in Asteraceae is furnished.
Keywords: Arnica-da-serra; bioactive terpenes; biosynthesis; combined omics